Impact of COVID-19 on Economic Activities and Poverty Threats in the Asia-Pacific Region - Saddam Rassanjani; Novialdi Risky; Dahlawi Maz; Wais Alqarni; Muhammad Achdan Tharis (Policy & Governance Review, 2021)
This paper discusses the impact caused by a virus outbreak called coronavirus disease (COVID-19). The virus initially appeared in Wuhan, China, in late 2019, then spread throughout the world, including the Asia-Pacific Region (APR). COVID-19 is believed to have damaged health and the global economy. Unlike the crisis that was caused by many previous disruptions, the impact caused by COVID-19 is wider and bigger. Many economic sectors have been paralyzed and suffered losses, such as production and trade. Export-import cooperation has become a dependency between countries, and this has also been hampered due to the rapid spread of this pandemic. Then, the closure of transportation access and the suggestion to stay at home has made the tourism sector sluggish. Meanwhile, another effect of this pandemic is the emergence of new poor groups due to the rise in layoffs. This study uses qualitative research methods to search for theoretical references relevant to cases or problems found in various works of literature, mainly scientific journals, books, reports, and actual and trusted news on the internet. This study aims to explore the potential of COVID-19 that not only threatens health, but also social, political, and economic spheres. From the analysis, it was concluded that COVID-19 could inhibit all global socio- economic activities that threaten the success of realizing Sustainable Development Goals (SDGs), but on the other hand, this pandemic can also be momentum for a more sustainable life order.